“THE ESSENCE OF THE CONCEPT OF SPIRITUAL EDUCATION AND FORMATION OF SKILLS OF YOUNG PEOPLE” IS HOW URGENT THE ISSUE OF EDUCATION IS IN TODAY’S RAPIDLY DEVELOPING ERA - Hayitov, Saidjon (Educational Research in Universal Sciences, 2023)
The peaceful life of the society is determined by the richness of the spiritual outlook of its members. This is evidenced by the history of civilizations that have reached many milestones in the history of mankind. Such characteristics are definitely formed in members of society through education. "Education is a practical pedagogical process aimed at forming certain physical, mental, moral and spiritual qualities in a person."